Pengaruh Kinerja Guru Terhadap Peningkatan Prestasi Belajar Siswa Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) SMP Negeri Bekasi - Syairul Bahar (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2021)
This study aims to determine the effect of teacher performance on improving student’s achievement in Social Sciences (IPS) subjects at SMPN Bekasi. The method used is a survey method. The results of this study indicate that there is an effect of teacher performance on improving student achievement in social studies subjects. This is evidenced by the t-count value of 2.160 with the t-table value of 1.658 and the probability value (sig.) of 0.04. Because the value of sig < 0.05 and t arithmetic > t table means that there is a significant effect of the teacher performance variable (X) on social studies learning achievement (Y). As a results, the teacher's performance from time to time must be improved. A teacher must have a commitment to continue learning, without it the teacher will be stunted in his/her knowledge and will be left behind in the midst of changing times that always increasing uncertainlly.